Effectiveness of Drone-Assisted Thiamethoxam12.6% + Lambda-Cyhalothrin 9.5% ZC against Pink Bollworm (Pectinophora gossypiella) in Cotton - , D P Padvi; , N K Bhute; , S T Aghav; , N K Medhe; , C B Wayal (Archives of Current Research International, 2025)
The field study was carried out at, AICCIP, MPKV, Rahuri-413 722 during Kharif, 2023. An investigation was undertaken with an objective, to evaluate the effect of Thiamethoxam 12.6% + Lambda-cyhalothrin 9.5% ZC insecticides against pink bollworm through drone application. The study was conducted using a randomized block design (RBD) with multiple insecticidal treatments, including drone and knapsack sprayer applications. The results revealed that among the tested insecticidal treatments Thiamethoxam 12.6% + Lambda-cyhalothrin 9.5% ZC @44 gm a.i./ha through drone application was recorded less rosette flower (4.42%), green boll damage(3.64%) and 2.11 pink bollworm larvae per 20 bolls. At harvest, the treatment recorded less open boll damage (6.68%) and locule damage (2.96%). The treatment @44 gm a.i./ha through knapsack sprayer found at par with it which had a non-significant difference among them. The treatment Thiamethoxam 12.6% + Lambda-cyhalothrin 9.5% ZC @55 gm a.i./ha through drone application was only for evaluation of phytotoxicity. These findings highlight the effectiveness of drone-based insecticide application as a promising tool for sustainable pest management in large-scale cotton farming.